Blending et analogie : enjeux épistémologiques - Mariangela Albano; Philippe Monneret (Corela)
This paper aims to put into perspective, through an epistemological approach the theories of blending (or “conceptual integration”, CI) and analogy. It is based on the integration of cognitive semantics approach (Fauconnier, 1985; Fauconnier and Turner, 1996, 1998 and 2002), analogical linguistics approach (Monneret 2004, 2014, 2017, 2018, 2019, 2021, 2023) and cognitive psychology approach (Gentner 1983; Gentner et al., 2001; Hofstadter, 2001; Hofstadter and Fluid Analogies Research Group 1995; Hofstadter and Sander, 2013). More specifically, the question posed is whether the analogical process underlies the formation and structuring of CI or whether CI is just a special case of analogical process. The paper will develop in three points i) an introduction to mental spaces and CI aimed at examining the place of analogy in the model; ii) a presentation of the analogical model in linguistics; iii) a comparison between the two models.